2009
DOI: 10.1002/fld.2100
|View full text |Cite
|
Sign up to set email alerts
|

QALE‐FEM for modelling 3D overturning waves

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. based on a fully nonlinear potential theory is presented in this paper. This development enables the QALE-FEM to deal with 3D (three dimensional) overturning waves over complex seabeds, which have not been considered since the method was devised by the authors of this paper in their previous works [1][2]. In order to tackle challenges associated with 3D overturning waves, two new numerical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…The notable papers based on particle methods for the topics related to wave-structure interactions include but are not limited to references [22][23][24] for using smoothed particle hydrodynamics (SPH), [25] for using moving particle semi-implicit method (MPS), [26][27] for using Meshless Local Petrov Galerkin with Rankine Source (MLPG_R). Some simplified test cases reported in the literature using these models showed a good agreement with the experimental measurements, see for example, [1][2][3][4][5][6][7][8][9][10]28] for the FNPT models and [22][23][24][25][29][30][31] for the NS models.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The notable papers based on particle methods for the topics related to wave-structure interactions include but are not limited to references [22][23][24] for using smoothed particle hydrodynamics (SPH), [25] for using moving particle semi-implicit method (MPS), [26][27] for using Meshless Local Petrov Galerkin with Rankine Source (MLPG_R). Some simplified test cases reported in the literature using these models showed a good agreement with the experimental measurements, see for example, [1][2][3][4][5][6][7][8][9][10]28] for the FNPT models and [22][23][24][25][29][30][31] for the NS models.…”
Section: Introductionmentioning
confidence: 68%
“…The FEM was used by Wu and Eatock Taylor [3] for the 2D cases and by Ma et al [4] for 3D cases, and it was further extended to handle complex objects and floating bodies simulations forming the QALE-FEM (Quasi-Arbitrary Lagrangian and Eulerian finite element method) by Ma et al [5,6], Yan et al [7,8,9] and SALE-FEM (SemiArbitrary Lagrangian and Eulerian finite element method) by Sriram [10], respectively. It has been shown that the FEM is more efficient for modelling strongly nonlinear waves while the BEM is more efficient for modelling linear or weak nonlinear problems [9]. The problems formulated by using the NS model are usually solved by employing a mesh-based method or a meshfree method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the QALE-FEM can model highly nonlinear free surfaces and three-dimensional overturning waves. The QALE-FEM method has been compared with experimental data and other numerical for wave breaking cases and found to be accurate 2010b). In all cases presented in this section, we use a water depth of 70 m. Average spatial discretization across the domain is 2.5 m, which reduced to approximately 0.8 m around the crest of the giant wave.…”
Section: Numerical Modelling Of the Draupner Wavementioning
confidence: 99%
“…In their approach, an in-house software package (QALE-FEM/FLOATMov) is combined with a commercial software, StarCD. The former is based on the FNPT model, which has been proven to be the fastest method for overturning waves [54,55]. The latter solves general ReynoldsAveraged Navier-Stokes (RANS) equations using the finite volume method.…”
Section: Introductionmentioning
confidence: 99%